The life of Pennsylvania Governor George M. Leader : challenging complacency - Wolensky, Kenneth C. (Lehigh University Press, 2011)
The Life of Pennsylvania Governor George M. Leader tells the story of George Michael Leader who, at 36 years old, was the second youngest governor ever elected to the office and served from 1955 to 1959. His chances at being elected were tenuous atbest: Democrats never fared well in pursuit of the Governor's Office in the Keystone State. His election was an upset. Republican Party stalwarts were stunned at the tally in Leader's favor. And, his election ushered in an era when the Commonwealth's electorate shifted its allegiance from majority Republican to majority Democrat, a trend that continu.